Saturation of the media with conspiracy narratives: content analysis of selected Polish news magazines - Czech, Franciszek (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2019)
The article has three dimensions: methodological, theoretical, and empirical. A point of departure for the methodological remarks is a characterization of the three main approaches in the vibrant interdisciplinary research field dealing with the phenomenon of conspiracy theories. In this context, the content analysis method is discussed as a promising approach to gain new data on conspiracy narratives. On the theoretical level, the concept of conspiracy narratives is discussed in reference to the popular understanding of the conspiracy theory. The main aim of the empirical part is determining to what extent the media are saturated with different kinds of conspiracy narratives. The analysis covers over 200 articles from two popular Polish news magazines (Sieci and the Polish edition of Newsweek) which occupy positions on opposite sides of the political divide in a society polarized, inter alia, by a conspiratorial suspicion that in 2010 an airplane carrying President Lech Kaczyński on board was deliberately crashed in Russia.

Artykuł ma trzy płaszczyzny: metodologiczną, teoretyczną i empiryczną. Punktem wyjścia do refleksji metodologicznej jest charakterystyka trzech głównych nurtów badawczych prowadzonych w ramach dynamicznie rozwijających się interdyscyplinarnych badań nad teoriami spiskowymi. Na takim tle omówiona jest analiza zawartości treści jako metoda badawcza pozwalająca w innowacyjny sposób uchwycić kluczowe zjawisko. W części teoretycznej przybliżona jest koncepcja narracji spiskowych w odniesieniu do potocznego rozumienia teorii spiskowych. Głównym celem części empirycznej jest określenie w jakim stopniu media są nasycone różnego rodzaju narracjami spiskowymi. Analiza obejmuje ponad 200 artykułów z dwóch opiniotwórczych tygodników („Sieci” i polska edycja „Newsweeka”), które znajdują się po dwóch stronach politycznego konfliktu w Polsce spolaryzowanych między innymi przez spiskowe podejrzenia dotyczące katastrofy prezydenckiego samolotu w 2010 roku w Rosji.
Nasycenie mediów teoriami spiskowymi. Analiza treści wybranych polskich tygodników
Keywords: conspiracy narratives; conspiracy theory; distrust; Poland; media; content analysis; teorie spiskowe; narracje spiskowe; Polska; media; analiza zawartości